Cognition, Mood and Sleep in Menopausal Transition: The Role of Menopause Hormone Therapy - Gava, Giulia (Medicina (Kaunas), 2019)
During the menopausal transition, which begins four to six years before cessation of menses, middle-aged women experience a progressive change in ovarian activity and a physiologic deterioration of hypothalamic-pituitary-ovarian axis function associated with fluctuating hormone levels. During this transition, women can suffer symptoms related to menopause (such as hot flushes, sleep disturbance, mood changes, memory complaints and vaginal dryness). Neurological symptoms such as sleep disturbance, “brain fog” and mood changes are a major complaint of women transitioning menopause, with a significant impact on their quality of life, productivity and physical health. In this paper, we consider the associations between menopausal stage and/or hormone levels and sleep problems, mood and reduced cognitive performance. The role of estrogen and menopause hormone therapy (MHT) in cognitive function, sleep and mood are also discussed.